Gender Stereotypes in Elementary School Textbooks in Indonesia: A Study of Visual and Narrative Representations - Yusri, Yusri (Indonesian Journal of Educational Studies, 2025)
Abstract. This study aims to identify and analyze gender stereotypes in elementary school textbooks in Indonesia by examining both visual and narrative representations. Employing a qualitative approach alongside content analysis methods, the research seeks to uncover how the roles, professions, and characteristics of men and women are depicted in educational materials. Data were collected using documentation techniques, focusing on the text and illustrations found in textbooks officially used in elementary schools, which were subsequently analyzed through a coding and interpretation process informed by representational and multimodal analysis. The results reveal that these textbooks consistently reinforce gender stereotypes. Firstly, the division of roles between men and women is portrayed along traditional lines, with men depicted as the central figures in productive activities and leadership. In contrast, women are relegated to domestic roles. Secondly, prestigious and technical professions are predominantly represented as male domains, whereas service-oriented and domestic roles are typically assigned to women, thereby limiting students' career aspirations based on gender. Thirdly, personality traits and characteristics are presented in a biased manner, with men characterized as strong, rational, and courageous, while women are portrayed as patient, emotional, and submissive. Overall, these representational patterns suggest that textbooks do more than convey academic content; they also serve as agents of gender socialization, potentially perpetuating gender inequality in education and social life. This research underscores the need to develop more gender-sensitive textbooks to foster an inclusive and egalitarian learning environment that nurtures the potential of all students, free from the constraints of stereotypes